ANALISIS PENERAPAN MODEL PEMBELAJARAN TERPADU TIPE WEBBED DALAM MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Hatima, Yoma; Fajrudin, Lili; Jatmiko, Andy Bayu; Jodiyariyan , Raka Azriel (Journal of Professional Elementary Education, 2025)
Research shows that primary school children need learning that encourages students to be more creative in exploring and discovering scientific concepts and principles deeply and authentically, both individually and in groups. In addition, learning that emphasizes direct student involvement in the learning process to ensure that students gain a more meaningful learning experience. Webbed type integrated learning model is one of the examples. Literature review was used as the method. The research stages began with article collection, reduction, performance, discussion, and conclusion. The research data sources are national journal articles in the last 4 years (2019-2023). Based on the results of the study, it shows that in applying the webbed type learning model in the classroom, it needs to be designed in advance in order to get good results, the steps are: (1) Theme Development, (2) Sub-Theme Development, (3) Learning Activity Development, (4) Use, (5) Media Monitoring and Reflection, (6) Teamwork Development, and (7) Evaluation